Phage Revolution Against Multidrug-Resistant Clinical Pathogens in Southeast Asia - Carascal, Mark B.; dela Cruz-Papa, Donna May; Remenyi, Roland; Cruz, Mely Cherrylynne B.; Destura, Raul V. (Frontiers in Microbiology, 2022)
Southeast Asia (SEA) can be considered a hotspot of antimicrobial resistance (AMR) worldwide. As recent surveillance efforts in the region reported the emergence of multidrug-resistant (MDR) pathogens, the pursuit of therapeutic alternatives against AMR becomes a matter of utmost importance. Phage therapy, or the use of bacterial viruses called bacteriophages to kill bacterial pathogens, is among the standout therapeutic prospects. This narrative review highlights the current understanding of phages and strategies for a phage revolution in SEA. We define phage revolution as the radical use of phage therapy in infectious disease treatment against MDR infections, considering the scientific and regulatory standpoints of the region. We present a three-phase strategy to encourage a phage revolution in the SEA clinical setting, which involves: (1) enhancing phage discovery and characterization efforts, (2) creating and implementing laboratory protocols and clinical guidelines for the evaluation of phage activity, and (3) adapting regulatory standards for therapeutic phage formulations. We hope that this review will open avenues for scientific and policy-based discussions on phage therapy in SEA and eventually lead the way to its fullest potential in countering the threat of MDR pathogens in the region and worldwide.